2012
DOI: 10.1007/s00253-012-4400-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dissolved hydrogen partial pressure on mixed culture fermentations

Abstract: Mixed culture fermentations are of interest for the low-cost production of organic acids from complex agricultural waste streams. Models are developed for these processes in order to predict the product spectrum as a function of the environmental process conditions. An important assumption in many existing models for anaerobic mixed culture fermentations is that the NADH/NAD(+) ratio is directly coupled to the dissolved hydrogen partial pressure (pH2, liquid). In this study, this assumption was tested experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Thermodynamic analysis of product formation pathways combined with product transport considerations enabled these authors to identify the optimal product spectrum in terms of bioenergy conservation potential. Based on experimental evidence (de Kok et al 2013) electron carriers other than NADH/NAD were included in the second version of the model , resulting in dominant production of butyrate and acetate mixtures as fermentation products. This fermentation pattern typically is associated with Clostridium fermentations that indeed are often found to dominate at acid and around neutral pH-values and mesophilic temperatures.…”
Section: Controlling the Product Spectrum In Anaerobic Fermentationsmentioning
confidence: 99%
“…Thermodynamic analysis of product formation pathways combined with product transport considerations enabled these authors to identify the optimal product spectrum in terms of bioenergy conservation potential. Based on experimental evidence (de Kok et al 2013) electron carriers other than NADH/NAD were included in the second version of the model , resulting in dominant production of butyrate and acetate mixtures as fermentation products. This fermentation pattern typically is associated with Clostridium fermentations that indeed are often found to dominate at acid and around neutral pH-values and mesophilic temperatures.…”
Section: Controlling the Product Spectrum In Anaerobic Fermentationsmentioning
confidence: 99%
“…Trend line is for ATP production at pH 8.00 only. propionate and ethanol at basic pH to butyrate at acidic pH may again result from the 6-105 maintenance energy) in the same way that a stable NAD pool is maintained 26 . This could imply that there are additional pH-related maintenance tasks at high pH, such as maintenance of the cellular membrane 185 , which require even greater ATP generation than does intracellular pH maintenance.…”
Section: Hpr-type Fermentationmentioning
confidence: 99%
“…Measurements of the redox states of bacterial EMCs have shown that the Fd and NADP pools are generally maintained at 90% or more reduced 42 , while the NAD pool is maintained at 80% or more oxidized 26,42 . This shifts the intracellular reduction potential of these EMCs down to around (vs SHE) -500 mV for Fd and -360 mV for NADP, while shifting NAD up to around -280 mV 43 .…”
Section: -6mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the unreliable product prediction under certain conditions, the interaction between microbial populations in MCF is also not well understood (Rafrafi et al, 2013. Thermodynamic was considered as the major driving force determining product mix and previously utilized to develop theoretical models for MCF (Costello et al, 1991, Mosey, 1983.As an example, pathways that produce more hydrogen (acetate type fermentation) are favoured at low hydrogen partial pressures (Ruzicka, 1996, de Kok et al, 2013. However, these models often fail in validating experiments, indicating that: (a) the full range of thermodynamic factors is not included, or (b) the influence of physiological and phylogenetic factors needs to be included.…”
Section: Application Barriers and Research Gapmentioning
confidence: 99%